Confirming the Reliability of the Maâ€™nÄ-cum-maghzÄ Approach to MansÅ«khah Verse: : Case Study of QS. Al-Baqarah (2): 240 - Azhar Amrullah Hafizh; Rusdiana Navlia; Muhammad Uzaer Damairi; Eko Zulfikar (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2025)
In the maâ€™nÄ-cum-maghzÄ approach to Qur'anic interpretation, Sahiron states that the paradigm that builds this approach is the absence of nasakh in the Qur'an. This raises questions about the existence of verses that are considered mansÅ«khah in the Qur'an, which for most tafsir scholars is positioned as a consensus. This article seeks to examine the reliability of the maâ€™nÄ-cum-maghzÄ approach, especially in the meaning and significance of verses that are considered mansÅ«khah by most scholars of interpretation and reveal the significance and meaning of QS. Al-Baqarah verse 240 regarding the length of the iddah period for women whose husbands die is one full year. This research is a type of library research with a maâ€™nÄ-cum-maghzÄ approach to the mansÅ«khah verse which is analyzed using content analysis. This study shows that, first, the ma'nÄ-cum-maghzÄ approach is quite reliable in interpreting QS. Al-Baqarah verse 240 because there are still scholars who interpret it based on negating nasakh, such as al-Tabari and al-Razi. In addition, the ma'nÄ-cum-maghzÄ approach reinforces the universal values contained in the Qur'an. Second, QS. Al-Baqarah verse 240 is a way for the Rasulullah Saw., gradually, to position women with dignity both economically and socially. This study contributes to strengthening the ma'nÄ-cum-maghzÄ approach, which can be a methodological alternative in reading verses that have been understood as mansÅ«khah, while also opening up space for a more contextual reading of the Qur'an that is gender-equitable and oriented towards universal ethical values.